Slovak System of Higher Education in its Connection to Society’s Transformations: Transition from Medieval Times to XXI Century European Integration - Myhovych, Iryna (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The article represents an attempt to investigate the development of the national higher education system of Slovak Republic (as part of former Czechoslovakia) starting from the first known data of the medieval times up to the beginning of the XXI century when the period of intense Europeanization and internationalization started. Considerable attention has also been paid to the development of higher education in Slovak Republic after 1989 with the emphasis on relevant legislation, students’ enrollment numbers, overall institutional setting. The aim of the paper is to present theoretical review of the Slovak national higher education system development as determined by the processes of socio-political transformations in the country, including the final stage integration to the European Union and European Higher Education Area (EHEA). Theoretical provisions of the paper are supported with relevant statistical data on the number of higher education institutions and the number of students, including the number of those who participate in mobility schemes within EHEA (statistical indicators are gender-sensitive). Attention has also been paid to development of the country’s higher education legislation system after the so-called disintegration of Czechoslovakia to Czech and Slovak Republics, which allowed for the establishment and development of private sector within national higher education system. The research is based on the comprehensive analysis of original sources – open-accessed national legal framework for higher education, as well as theoretical and practical research works by Slovak scholars. The topicality of research is determined by the similarity of the Slovak and Ukrainian national systems of higher education at the end of the XX century, which allows to state that consideration of the Slovak context is relevant to the current reforming Ukrainian national higher education system.